Misinterpretation of Psychiatric Illness in Deaf Patients: Two Case Reports - Ethan Anglemyer; Craig Crespi (Case Reports in Psychiatry)
The Deaf/hard of hearing population is growing rapidly and the medical community is facing a higher demand for this special needs group. The Deaf culture is unique in that spoken word is via sign language. What one person may see as mania or psychosis is actually a norm with Deaf individuals. The fear of the unknown language often creates immediate conclusions that are false. As such, being culturally sensitive becomes a large component of properly assessing a Deaf patient in any psychiatric situation. In the first case, the patient is a 26-year-old prelingually Deaf male, who was placed under an involuntary hold by the emergency room physician for acting erratic and appearing to respond to internal stimuli. The patient was later interviewed with an interpreter and stated he became upset because the staff was not providing him proper care as they lacked an ability to communicate with him. The patient’s family was called who corroborated the story and requested he be discharged. Case two presents with a 30-year-old Hispanic male who is also prelingually Deaf. He was admitted involuntary for bizarre behavior and delusions, with a past diagnosis of schizophrenia. Upon interview, the patient endorsed delusions via written language; however, through an ASL-language interpreter he was able to convey a linear and coherent thought process. Caring for special needs patients must be in the repertoire of any trained healthcare professional. Deaf Individuals experience mental illness just like the general population. Symptoms such as auditory hallucinations are not brought up in the same manner and are thought to be a visual construct interpreted by the patient as a vocal expression. It is imperative that these subtle differences are known in order to differentiate out an actual mental illness. In any case where language is a barrier, an interpreter must be present for a thorough assessment. These cases lend further thought into policy reform for Deaf individuals within healthcare.